Developing a subpopulation-based model for the olive fruit fly Bactrocera oleae (Diptera: Tephritidae): conceptual model out-line - Paz, Maria Catarina (2021)
Bactrocera oleae Rossi (olive fruit fly) is a dipteran of the family Tephritidae, considered the key pest of olives in Mediterranean countries, where it causes losses of great economic impact. Nat ural pest control is an important alternative or complement to the use of plant protection products against B. oleae. This is an ecosystem service that can be enhanced if we are able to predict its behav ior, which can be done through computer models simulating interactions between animals, agricul tural management and climate. In this paper we present the conceptual model of a spatially explicit subpopulation-based model being developed for B. oleae in olive groves. In this modelling tech nique, the simulated dynamic landscape is segmented into non-overlapping cells, where the sub populations of B. oleae are represented as separate but interacting entities. Our model is based on the Animal Landscape Man Simulation System (ALMaSS), which comprises a highly detailed and realistic landscape representation, incorporating data on different aspects of farm management, crop development, and climate, and where simulated entities operate. We present the general out line of B. oleae’s life cycle, as well as succinct information on how these organisms interact with their environment. This is a step for the development of the final model and its implementation in AL MaSS.